Stimuli‐Responsive Electrodes Detect Oxidative Stress and Liver Injury. (23rd December 2014) - Aran, Kiana; Parades, Jacobo; Rafi, Mohammad; Yau, Jennifer F.; Acharya, Abhinav P.; Zibinsky, Mikhail; Liepmann, Dorian; Murthy, Niren
<x xml:space="preserve">Abstract</x> A digital point‐of‐care biosensor for measuring reactive oxygen species is presented based on novel reactive oxygen species responsive polymer‐based electrodes. The biosensor is able to detect a drug‐induced liver injury by monitoring the oxidative stress in the blood. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>